Isotopic Transient Kinetic Analysis of Soot Oxidation on Mn3O4, Mn3O4-CeO2, and CeO2 Catalysts in Tight Contact Conditions - Marek Rotko; Karolina Karpińska-Wlizło (Molecules)
The reaction mechanism of soot oxidation on Mn (Mn3O4), Mn-Ce (Mn3O4-CeO2), and Ce (CeO2) catalysts in tight contact conditions was investigated using ITKA (isotopic transient kinetic analysis). The obtained results suggest that lattice-bulk oxygen from all studied catalysts takes part in the soot oxidation process but with varying relative contributions: for the Ce catalyst, this contribution is practically 100%, whereas with decreasing Ce content in Mn-Ce catalysts, the significance of lattice-bulk oxygen for soot oxidation diminishes. For the Mn catalyst, it is estimated to be below 50%. Moreover, strong interactions between Mn and Ce ions were observed, increasing oxygen mobility in the catalyst crystal lattice and affecting the activity of Mn-Ce catalysts.